Combining superselective catheterization and electrochemotherapy: A new technological approach to the treatment of high-flow head and neck vascular malformations - Krt, Aljosa; Cemazar, Maja; Lovric, Dimitrij; Sersa, Gregor; Jamsek, Crt; Groselj, Ales (Frontiers in Oncology, 2022)
Introduction: The study aims to demonstrate a combination of superselective catheterization and electrochemotherapy as a feasible and effective new technological approach in treating high-flow vascular malformations of the head and neck region. Patients and methods: In the patient with high-flow arteriovenous malformation of the lower lip, superselective catheterization was performed under general anesthesia. The microcatheter was used to administer 750 IU BLM intra-arterially into the feeding vessel. The whole malformation surface was then covered with 15 applications of electric pulses using the plate electrode. Results: Excellent response, without functional or aesthetic deficits, was obtained in 10 weeks. During this period, debridement and necrectomy were performed regularly on follow-up visits. The pain was managed with oral paracetamol and sodium metamizole. Conclusion: Combining electrochemotherapy using bleomycin with superselective catheterization and arteriography is a feasible treatment option for high-flow vascular malformations in the head and neck region and could play a significant role in managing these challenging lesions.